Memahami Fenomena Konten Sedekah dalam Perspektif Matius 6:1-4 - Bonifasius Pradipta Putra Alam; Ireneus Yongki Artha Pieter (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
Almsgiving content on various social media platforms is an interesting social phenomenon to study, especially based on the perspective of Matthew 6:1-4. As a text that is influenced by the background of religious and cultural communities, Matthew has a unique way of maintaining the continuity of the ideals of his community. An interpretation model that utilizes the help of social sciences will be beneficial in understanding the ideals of the community that influenced Matthew. From the results of applying the social science way of thinking to the text of Mat 6:1-4, two important things must be understood. First, the teaching of almsgiving is a religious obligation. Second, the teachings on almsgiving aim to create “an egalitarian society” and avoid damaging the recipient's reputation socially, culturally, or religiously. Almsgiving content featuring fictitious and animated characters and storylines is offered as an alternative to responding to this phenomenon.